ANALISIS HUKUM KELALAIAN PEMBUATAN AKTA WASIAT OLEH NOTARIS - Siregar, Maria Magdalena; Aarce Tehupeiory; L Elly AM Pandiangan (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
Land is an important part of human life, there are many things that humans can do related to land, such as residences built on land or plantations to fulfill human needs or even make businesses on land to use the material results by humans. Therefore land has a lot of influence in legal actions in human life. One of them is the transfer of land rights in the form of a testamentary grant which is related to a will deed. In making this will, there were many violations in the procedure for the process of making it by a notary. The formulation of the problem in this thesis is what is the procedure for making a will by a notary and what are the legal consequences for negligence in making a will by a notary. This research is a normative legal research with the statutory approach/statute approach and the case approach. The data used in this study is secondary data in the form of primary legal material, namely the Civil Law, Law No. 5 of 1960 concerning Basic Basic Regulations - Principal Agrarian, Regulation of the Minister of Law and Human Rights No. 60 of 2016 concerning Procedures for Reporting will and request for the issuance of Electronic Testament Certificate, Law No. 2 of 2014 concerning Amendments to Law No. 30 of 2004 concerning Notary Position, Notary Code of Ethics for Indonesian Notary Association, while secondary legal materials are books, journals or other literature, tertiary legal materials in the form of dictionaries, then the legal material collected is compiled and analyzed. From the results of this study it can be concluded that in making a will, a notary needs to make it in accordance with the provisions of the procedures for the process of making a deed and the conditions for making a will as stipulated in the Civil Code, Notary Code of Ethics and other legislation. If the notary is negligent in making it by not fulfilling all the conditions or in making it not in accordance with the making procedure, the notary is deemed to have committed an offense due to a lack of caution in making a will. As a result of this negligence, the notary will be given sanctions both in criminal law, civil law and administratively in accordance with the lawsuit from the injured victim or plaintiff and the will will be considered inauthentic or become an underhanded deed or null or void by law. That is why a notary needs to carry out obligations in accordance with applicable provisions, especially in making a testamentary deed so that the deed of will remains authentic and avoids breach of office by a notary.